Teachers’ Perceptions of Ethical Social Media Use for Senior High School Students in West Java - Rizal Kailani; Rudi Susilana; Mohammad Ali; Laksmi Dewi (AIBPM Publisher, 2026)
As social media becomes more common in schools, it is important to be aware of ethics in order to encourage responsible digital behavior. This study seeks to investigate teachers' perceptions of digital ethics regarding social media usage among senior high school students in West Java. A quantitative survey design was utilized, encompassing 360 Religious and Character Education teachers chosen via multistage random sampling. A 33-item questionnaire was used to collect data on seven aspects of digital ethics. The answers were measured on a 5-point Likert scale. The results show that there is a high level of agreement on all dimensions (mean range: 4.13–4.51), which means that people really understand digital ethics. Justice and equality (M = 4.51) and respect for human rights (M = 4.51) were the most highly rated dimensions. Ethical data practices (M = 4.27) got the lowest score. There were only small differences between demographic groups. These results show how important it is to include digital ethics in school curricula, especially in areas that are not as well-known, like data ethics and sustainability, to help students become better digital citizens.